Cidades inteligentes: entraves tecnológicos ou desenvolvimento para a sociedade? Estudo de caso Programa Sandbox Vila A Inteligente do município de Foz do Iguaçu-PR - Kazama, Márcio (2023)
The Vila A neighborhood, in Foz do Iguaçu-PR city, is Brazil's first Smart Cities Sandbox, characterized as an experimental space for technical and technological validation of solutions for Smart Cities, known as the Vila A Inteligente Program. In this sense, this dissertation, in partnership between Unioeste and Itaipu Technology Park aimed at analyzing the neighborhood residents’ perception about the technological interventions that were carried out by the Sandbox Program - Foz do Iguaçu. This study is therefore justified by the lack of discussions on inclusion and social participation among the ones the produce technologies or interveners and society. This is a case study, configured as an applied research that used exploratory and descriptive methods, with a qualitative approach. Regarding data collection procedures, there was not only a bibliographical research, but also a survey of organization records and structured interviews using questionnaires with 292 interviewees, including residents, workers, students and passersby who belong to the ecosystem Program in the Neighborhood. Content analysis was applied to analyze the obtained data. Thus, after analyzing the information gathered and identifying the relevant points, the results were presented in correlation with the theoretical reference. They have shown that the population has a limited understanding concerning the interventions purpose and technological barriers. Other observations are also associated to the assertion that the population was not queried about the problems, needs and desires of the neighborhood. Ergo, the Program has been set up, in a loss-making way, according to the residents’ answers to local and social problems. It can be highlighted that there was a clear misalignment between management and its responsibilities in relation to the Program, especially in terms of communication, publicity, transparency, democracy, inclusion policies, community participation and engagement. On the other hand, a significant number of interviewees have observed the interventions/technologies as promoting development tools in the region. Therefore, based on this perspective, this topic makes further studies possible, and can contribute to governance on population’s real needs. So, better strategies can be provided in public policy and development issues, related on intelligent technologies and, mainly, on intelligent governance.